Analisis Pengaruh Karakteristik , Leverage dan GCG Perusahaan Manufaktur Sektor Basic Industry dan Chemical serta Consumer Goods yang Listing di BEI Periode 20130-2016 terhadap Tax Avoidance - Steven Darmawan; Hari Hananto (Akuntansi dan Teknologi Informasi, 2018)
The objective of the research is to observe the effect of characteristic, leverage and corporate governance to tax avoidance in manufacturing company listed in BEI from 2013-2016. Population in this research consists of 109 companies. The test of hypothesis in this research uses regression linier analysis. The result of this research shows that capital intensity and ROA have significant effect to tax avoidance, while size, leverage, sales growth, corporate governance don’t have significant effect to tax avoidance.